Comparison of biomechanical parameters in lower limb joints of stroke patients according to conventional evaluation scores during level walking - Jeon, HyeongMin; Chung, Eun-Hye; Bak, Se-Young; Kim, Heegoo; Shin, Seyoung; Baek, Hongseok; Kim, MinYoung (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Patients with chronic stroke capable of independent gait were classified into Functional Ambulation Category (FAC) 4 or 5 and the kinetic and kinematic data from their lower limb joints on the affected and unaffected sides were compared with that of healthy individuals. Finally, the qualitative changes in the gait of patients with stroke were investigated based on the differences in FAC scores. Methods: Twelve healthy participants and 19 patients with stroke capable of independent gait were included. The 3D motion analysis and conventional assessment were measured for all patients with stroke. Results: The FAC 5 group exhibited a larger ROM than the FAC 4 group in knee and hip joints on the affected side and only in the hip on the unaffected side. In the FAC 5 group, ROM differences with the healthy group on either the affected or unaffected side were absent. The peak of the hip flexion moment on the affected side in both the FAC 4 and 5 groups was smaller than in the healthy group and in the FAC 4 group on the unaffected side. The absorption power min on the affected side was smaller only in the FAC 4 group than in the healthy group and was larger in the FAC 5 group than in the FAC 4 group. On the unaffected side, the absorption power min was smaller only in the FAC 4 group than in the healthy group. Conclusion: Functional differences in gait were found in patients classified based on conventional evaluation capable of independent gait after post-stroke rehabilitation. Patients may not exhibit complete recovery in the kinetic indices even if they are judged to be normal in the conventional evaluation and the kinematic gait indices indicate recovery. Evaluating kinetic indices in addition to kinematic indices is necessary, and joint power may be an especially useful index.